Pareto on Marshall's Demand Curve - Wilson, Edwin B. (Quarterly Journal of Economics, 1943)
Journal Article Pareto on Marshall's Demand Curve Get access Edwind B. Wilson Edwind B. Wilson Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 58, Issue 1, December 1943, Pages 141–145, https://doi.org/10.2307/1885761 Published: 01 December 1943